2019
DOI: 10.3390/children6030036
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Linkage between Exposure to Violence and Victimization, Coping, and Adjustment among Urban Youth: Findings from a Research Study on Adolescents

Abstract: From examinations of the literature on the influence that exposure to violence and coping strategies have on delinquent behavior and emotional outcomes, this study addresses the association between violent victimization and the moderating effects of coping strategies among 500 African-American adolescents who exhibit both externalizing behaviors such as delinquency and internalizing symptoms, including anxiety and depression. The investigation examines the development of the aforementioned adjustment problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(34 reference statements)
1
1
0
Order By: Relevance
“…Although our 2017 study confirmed the mediating role of peer factors (e.g., deviant peer affiliation) in the relationship between community violence exposure and externalizing problem behaviors, which was consistent with previous studies (Goodearl et al, 2013;Hinnant et al, 2019), and the negative effect of CVE on externalizing problem behaviors in adolescents has been documented (Ziv, 2012;Lepore and Kliewer, 2013;Fagan et al, 2014;Stoddard et al, 2015;McGee et al, 2019), the moderating role of parental factors is still unclear. Although in our previous studies, we noted that school climate was a very important covariable for the moderating effect.…”
Section: Discussionsupporting
confidence: 89%
“…Although our 2017 study confirmed the mediating role of peer factors (e.g., deviant peer affiliation) in the relationship between community violence exposure and externalizing problem behaviors, which was consistent with previous studies (Goodearl et al, 2013;Hinnant et al, 2019), and the negative effect of CVE on externalizing problem behaviors in adolescents has been documented (Ziv, 2012;Lepore and Kliewer, 2013;Fagan et al, 2014;Stoddard et al, 2015;McGee et al, 2019), the moderating role of parental factors is still unclear. Although in our previous studies, we noted that school climate was a very important covariable for the moderating effect.…”
Section: Discussionsupporting
confidence: 89%
“…These results are in line with those from studies such as [3], which show a correlation between protective factors and a reduction in ACLs involvement in criminal activities. Thus, an accumulation of protective factors is fundamental [46] not only to guard against antisocial patterns of behavior [47][48][49][50][51] but also as a predictor of behaviors unconnected with criminal-type dynamics. An accumulation of variables that predict risk, however, makes it possible to determine with greater accuracy any antisocial behaviors that could, if not stopped, continue into adulthood.…”
Section: Discussionmentioning
confidence: 99%